Game-Based Learning with Educandy to Improve Indonesian Language Learning Outcomes of Grade V Elementary School Students - Kurniawan, Afdal; Feronika, Afrilia; Liandri, Tasha Wulandari; Puspita, Tiara Indrajava; Novianti, Tiara; Sagita, Tika; Reinita, Reinita; Salmaini, Salmaini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The rapid advancement of digital technology has driven transformation in the educational landscape, particularly at the elementary school level. One emerging innovation is the use of game-based learning (GBL) media through platforms such as Educandy. This study aims to examine the effectiveness of using Educandy to improve Indonesian language learning outcomes among fifth-grade elementary school students. The methodology employed is a descriptive qualitative literature analysis (Systematic Literature Review). A number of relevant national and international papers served as data sources. According to the findings, the use of Educandy can significantly enhance learning outcomes, student motivation, and active engagement. Compared to traditional approaches, Educandy offers a more engaging and dynamic learning environment. However, there are challenges, including dependence on electronic devices and internet connectivity. In conclusion, Educandy is a useful and relevant learning tool that can be effectively used in elementary classrooms for teaching the Indonesian language.